CRISPR/Cas12a-based technology: A powerful tool for biosensing in food safety. (April 2022) - Mao, Zefeng; Chen, Ruipeng; Wang, Xiaojuan; Zhou, Zixuan; Peng, Yuan; Li, Shuang; Han, Dianpeng; Li, Sen; Wang, Yu; Han, Tie; Liang, Jun; Ren, Shuyue; et al.
Abstract: Background: In the context of the current pandemic caused by the novel coronavirus, molecular detection is not limited to the clinical laboratory, but also faces the challenge of the complex and variable real-time detection fields. A series of novel coronavirus events were detected in the process of food cold chain packaging and transportation, making the application of molecular diagnosis in food processing, packaging, transportation, and other links urgent. There is an urgent need for a rapid detection technology that can adapt to the diversity and complexity of food safety. Scope and approach: This review introduces a new molecular diagnostic technology-biosensor analysis technology based on CRISPR-Cas12a. Systematic clarification of its development process and detection principles. It summarizes and systematically organizes its applications in viruses, food-borne pathogenic bacteria, small molecule detection, etc. In the past four years, which provides a brand-new and comprehensive solution for food detection. Finally, this article puts forward the challenges and the prospects for food safety. Key findings and conclusions: The novel coronavirus hazards infiltrated every step of the food industry, from processing to packaging to transportation. The biosensor analytical technology based on CRISPR-Cas12a has great potential in the qualitative and quantitative analysis of infectious pathogens. CRISPR-Cas12a can effectively identify the presence of the specific nucleic acid targets and the small changes in sequences, which is particularly important for nucleic acid identification and pathogen detection. In addition, the CRISPR-Cas12a method can be adjusted and reconfigured within days to detect other viruses, providing equipment for nucleic acid diagnostics in the field of food safety. The future work will focus on the development of portable microfluidic devices for multiple detection. Shao et al. employed physical separation methods to separate Cas proteins in different microfluidic channels to achieve multiple detection, and each channel simultaneously detected different targets by adding crRNA with different spacer sequences. Although CRISPR-Cas12a technology has outstanding advantages in detection, there are several technical barriers in the transformation from emerging technologies to practical applications. The newly developed CRISPR-Cas12a-based applications and methods promote the development of numerous diagnostic and detection solutions, and have great potential in medical diagnosis, environmental monitoring, and especially food detection. Graphical abstract: CRISPR-Cas12a-based systems for biosensors. Image 1 Highlights: The complexity of the current food safety situation includes viruses, pathogenic bacteria, and small molecule detection. The emergence of CRISPR-Cas12a analysis technology can provide a good solution for it. The recent advances in CRISPR-Cas12a mediated biosensors and their applications in the detection of viruses, food-borne pathogens, small molecules were reviewed. The basic principle of CRISPR-Cas12a for analysis technology was illustrated, and these sensors were classified based on different detection principles and targets. Several representative new detection devices based on CRISPR-Cas12a were presented. The current problems, challenges and the future development of CRISPR-Cas12a biosensor were summarized and prospected.